Analysis of Tax Liability Avoidance Based on Islamic Economics in West Java - Afwa, Atiqah Ummu; Mubina, Diani Illahi; Puspita, Dita; Adisha, Najma; Chaerani, Sabila; Supriyadi, Tedi (Al-Sharf: Jurnal Ekonomi Islam, 2025)
This study aims to examine tax avoidance from an Islamic economic perspective by focusing on the principles of justice, openness, and social responsibility. The method used in this study is qualitative with a literature study approach. The findings show that the practice of changing financial reports and exploiting loopholes in taxation are included in the prohibited categories, namely tadlis and gharar, according to Islam. Injustice in the tax system results in decreased public trust in the government and increases economic inequality.